FAVIPIRAVIR EFFICACY AND SAFETY FOR THE TREATMENT OF SEVERE CORONAVIRUS 2019. A RETROSPECTIVE STUDY. - Waleed Aletreby,; Basheer Abdulrahman,; Ahmed Mady,; Mohammed Al-Odat,; Ashraf Al Tayar,; Muhammad Asim Rana,; Abdulrahman Alharthy,; Alyaa Alhazmi,; Ahmed Abdelmoaty,; Muhammad Mansoor Hafeez,; Ahmed Kuhail,; Alfateh Noor,; et al. (Journal of Ayub Medical College Abbottabad, 2022)
Background: Corona virus disease is caused by the enveloped, single stranded RNA virus known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) becoming the deadliest disease of the century. Its global outbreak has led researchers to develop drugs or vaccines to prevent the spread of the disease. Favipiravir is an approved orally administered antiviral drug that selectively inhibits RNA-dependent RNA polymerase, used off-label to treat COVID-19. Objectives: The purpose of this study was to assess the efficacy and safety of this drug for severe COVID-19 infection. Methods: This was an observational retrospective study, carried out at the ICU of King Saud Medical City (KSMC) from June 2020 to August 2020. Including a total of one thousand six hundred and ninety-nine patients (n=1699). Categorized into a treatment group (193 patients) who received Favipiravir along with standard care, and non-treatment group (1506 patients) who received standard care only. Results: ICU all-cause mortality was similar in both groups i.e., (Treated group 38.3% Vs Untreated group 39.4%, 95% CI of difference: -6.6% to +8.4%; p = 0.8). The subgroup analysis of survivors as compared to deceased in the treatment group showed that survivors had significantly lower age, international normalising ratio (INR), blood urea nitrogen (BUN), and creatinine. The mean ICU length of stay (LOS) was shorter for survivors compared to deceased (11.2± 8.03 Vs 16.7±9.8 days respectively), while hospital LOS was almost similar between the two groups. Advanced age (OR 1.03 [95% CI: 1.01-1.06]; p=0.004), higher INR and BUN were significantly associated with increased odds of mortality. Comparison of lab investigations at day 1 and day 10 in the treatment group (regardless of outcome) showed that there was a significant increase in Alanine transaminase (ALT), alkaline phosphatase (ALK), and Bilirubin, while an insignificant trend of increase in Aspartate transaminase (AST) and creatinine was recorded. Conclusion: In this study, Favipiravir showed better therapeutic responses in patients with severe COVID-19 infection, in terms of average duration of stay in the intensive care unit and was well tolerated in the younger age, but showed no mortality benefit. However, elevated levels of inflammatory markers, including increased ALT, AST, BUN, bilirubin, and creatinine, needs to be carefully examined.